Efficiency Of Using Steel End Caps In Improving The Post-Fire Flexural Behavior Of Frp Reinforced Concrete Beams - Hamad, Rami J. A. (2017)
The use of Fiber Reinforced Polymer (FRP) bars as an alternative to traditional steel reinforcement helps overcoming durability problems in reinforced concrete structures. The behavior of FRP-RC structures is satisfactory at only low temperatures, hence the application of combustible FRP materials in commercial, industrial and residential buildings, where the possibility of fire occurrence is relatively high, can be dangerous. Further research to evaluate and enhance the performance of FRP-RC structures under fire conditions is required. In this study, the effect of high temperatures on the mechanical properties of FRP/Steel bars, bond behavior between FRP/Steel bars and concrete, and the flexural response of concrete beams with different types of FRP bar reinforcement was investigated in much details. A new steel-end-caps technique was proposed aiming to improve anchorage of embedded FRP bars in concrete. For that FRP/Steel bars, plain concrete, pullout and beam specimens (with and without steel end caps) were prepared and then cured for 28 days and later tested before and after subjected to elevated temperatures of up to 500°C. Concrete and FRP bars suffered significant reductions in their mechanical properties due to exposure to high temperatures. Bond strength between FRP bars and concrete had decreased upon exposure to temperature in the range of 125 to 325°C, with the reduction reaching as high as 85%. These reductions were reflected negatively in the behavior of heated FRP-RC beams hence cracking load, ultimate load capacity, stiffness and total absorbed energy were reduced by as high as 89%, 81%, 79%, and 70%, respectively whereas mid-span deflections and ductility indices were increased noticeably by as high as 50% and 94%, respectively. Attaching steel end caps to the ends of FRP bars had improved their bond strength with concrete before and after exposure to high temperatures of up to 325oC. Consequently, the flexural performance of FRP-RC beams with end-cap anchorage was improved where the cracking load, ultimate load capacity, stiffness, deflection at ultimate load, and total absorbed energy were increased to reach as high as (124%, 208%, 225%, 196%, and 453%) and (33%, 123%, 58%, 216% and 215%) before and after heating up to 500°C, respectively, compared with that of control beams without end anchorage. Based on the experimental results, an analytical model was proposed to predict the behavior of the ascending part of bondslip relation between the different FRP bars and concrete under high temperatures. Another theoretical method was also proposed to predict the theoretical ultimate load capacity of FRP-RC beams. The predictions of the two models were in an excellent agreement with the experimental results.